2004
DOI: 10.1097/00004694-200411000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiolucent and Fracture Tables in the Treatment of Slipped Capital Femoral Epiphysis

Abstract: A retrospective study was undertaken to see whether there was any difference in the time required and the accuracy of pin placement between slips pinned on a fracture table and those pinned on a radiolucent table. All patients were treated by single screw fixation of stable slipped capital femoral epiphysis (SCFE), 36 on a fracture table and 29 on a radiolucent table. Mean operating room time on the fracture table (63 minutes) was greater than that on the radiolucent table (51.2 minutes) (P <0.05). Mean surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Blasier [10] showed that operating time was prolonged significantly when a fracture table was used but with no significant difference in screw position in a group of stable SCFE. This could be different for the unstable slip.…”
Section: Discussionmentioning
confidence: 99%
“…Blasier [10] showed that operating time was prolonged significantly when a fracture table was used but with no significant difference in screw position in a group of stable SCFE. This could be different for the unstable slip.…”
Section: Discussionmentioning
confidence: 99%
“…In-situ pinning, the standard treatment for a SCFE hip, is a radiographic technique where multiple images using an image intensifier may be necessary. The procedure can be performed using a traction table [2][3][4] or a radiolucent table [5][6][7].…”
Section: Introductionmentioning
confidence: 99%